Forecast of Copper Price Series Using Vector Support Machines - Soto-Gomez, J; Carrasco-Armijo, R (Institute of Electrical and Electronics Engineers Inc., 2018)
We research the potential of Support Vector Machines (SVMs) for forecasting in chaotic series of copper s price; based on different combination of structure, and possibilities of discovering knowledge in big data. It was built models of SVMs to forecast the copper s price of the London Metal Exchange (LME). © 2018 IEEE.